ATMOSFER PIDANA DALAM PERDATA - Maniur Sinaga (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Criminal law and civil law are two legal domains with different functions, objectives, and enforcement mechanisms in the Indonesian legal system. However, in law enforcement practice, a phenomenon known as a criminal atmosphere in civil law often occurs, namely a condition where a civil dispute is accompanied by or transferred to a criminal process. This phenomenon gives rise to various legal issues, ranging from legal uncertainty, the potential criminalization of civil disputes, to violations of the principles of justice and human rights. This study aims to examine the concept of a criminal atmosphere in civil cases, identify the factors causing the transfer of cases from the civil to the criminal realm, and analyze the resulting legal and social impacts. This study uses a normative juridical method with a conceptual approach and legislation, supported by a study of relevant court decisions. The results show that the transfer of civil cases to criminal cases is generally triggered by the misuse of criminal articles, a weak understanding of law enforcement officials regarding the boundaries of breach of contract and criminal acts, and public perception that the criminal route is more effective. The existence of the element of mens rea and the application of the principle of ultimum remedium are the main keys in determining the legal qualification of an act. This study emphasizes the importance of strengthening the principle of ultimum remedium, protection of rights through legal aid, and the professionalism of law enforcement officers to prevent the criminalization of civil disputes and maintain legal certainty and justice in the Indonesian justice system.